How justice becomes part of the deal: pre-conditions for the inclusion of transitional justice provisions in peace agreements - Leib, Julia (International journal of transitional justice, 2022)
In which negotiation contexts are transitional justice provisions included in peace agreements? Today, many peace agreements include transitional justice provisions, but their inclusion differs based on conflict and negotiation characteristics. While context thus seems to be relevant for the choice of transitional justice provisions agreed on by the warring parties, very little is known about the context clusters that enable transitional justice. Using data on 58 full peace agreements signed between 1989 and 2018, a crisp-set Qualitative Comparative Analysis (QCA) investigates the combinations of conflict intensity, rebel group strength, type of conflict, third-party support and civil society participation that led to the inclusion of transitional justice provisions. The result of this exploratory study suggests four context settings that are identified as being empirically relevant for the inclusion of transitional justice provisions. Choices of justice are thus the result of an overall negotiation environment characterized by multiple interrelated context factors.